N2O–Assisted Siphon Foaming of Modified Galactoglucomannans With Cellulose Nanofibers - Nypelö, Tiina; Fredriksson, Jessica; Arumughan, Vishnu; Larsson, Emanuel; Hall, Stephen A.; Larsson, Anette (Frontiers in Chemical Engineering, 2021)
Foaming of most bio-based polymers is challenged by low pore formation and foam stability. At the same time, the developing utilization of bio-based materials for the circular economy is placing new demands for easily processable, low-density materials from renewable raw materials. In this work, we investigate cellulose nanofiber (CNF) foams in which foaming is facilitated with wood-based hemicelluloses, galactoglucomannans (GGMs). Interfacial activity of the GGM is modulated via modification of the molecule’s amphiphilicity, where the surface tension is decreased from approximately 70 to 30 mN m−1 for unmodified and modified GGM, respectively. The chemical modification of GGMs by substitution with butyl glycidyl ether increased the molecule’s hydrophobicity and interaction with the nanocellulose component. The highest specific foam volume using 1 wt% CNF was achieved when modified GGM was added (3.1 ml g−1), compared to unmodified GGM with CNF (2.1 ml g−1). An amount of 96 and 98% of the GGM and GGM-BGE foams were lost after 15 min of foaming while the GGM and GGM-BGE with cellulose nanofibers lost only 33 and 28% of the foam respectively. In the case of GGM-BGE, the foam stability increased with increasing nanofiber concentration. This suggests that the altered hydrophobicity facilitated increased foam formation when the additive was incorporated in the CNF suspension and foamed with nitrous oxide (N2O). Thus, the hydrophobic character of the modified GGM was a necessity for foam formation and stability while the CNFs were needed for generating a self-standing foam structure.